ANALISIS SIKAP NASIONALISME MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA MATERI PANCASILA DALAM KEHIDUPAN SISWA KELAS V MIS ISLAMIYAH KALIANGKUP - Wahyu Agi Widodo; Suyoto; Arum Ratnaningsih (STKIP Subang, 2025)
Analysis of Nationalist Attitudes Through Pancasila Education Learning PancasilaMaterial in the Lives of Class V Students of MIS Islamiyah Kaliangkup”. ElementarySchool Teacher Education. FKIP, Muhammadiyah University of Purworejo. 2025.The aim of the research was to analyze nationalist attitudes through PancasilaEducation learning in class V students of MIS Islamiyah Kaliangkup.This study used a qualitative approach. The subjects were fifth-grade elementaryschool students in the 2024/2025 academic year. The data sources were primaryand secondary data. Data collection techniques included observation, interviews,and documentation. The data collection instruments were based on indicators ofnationalist attitudes at the elementary school level. Data analysis techniquesincluded data collection, data presentation, and conclusion drawing.The results of this study indicate that AF students have not fulfilled the indicators oflove for the homeland, LQ have not fulfilled the indicators of pride as an Indonesiannation, MR have not fulfilled the indicators of love for the homeland, MF have notfulfilled the indicators of love for the homeland, RWP have not fulfilled the indicatorsof pride as an Indonesian nation, love for the homeland, and prioritizing publicinterests, AYA have not fulfilled the indicators of prioritizing public interests, SFHhave not fulfilled the indicators of prioritizing public interests, SMLK have not fulfilledthe indicators of love for the homeland. It can be concluded that there are twostudents out of twelve students who do not always or sometimes use good andcorrect Indonesian, four out of twelve students do not always or sometimesmemorize and can sing national songs and regional songs, there are four out oftwelve students who do not always or sometimes speak politely to teachers andfriends.